African-American Male Identities in Adult Basic Education and Literacy Programs [Theorizing from the Literature] - Brendaly Drayton (Adult Education Research Conference, 2010)
This paper proposes that the relationship between literacy and identity holds potential for illuminating African-American men’s participation in ABEL programs and providing opportunities for learning.